ProtectaBEE® and bee vectoring: innovating hive-based health with inspensing technology for sustainable apiculture - Shelley, Erica; Brown, Tasmin; Karthikeyan, Aparna; Kevan, Peter (Frontiers in Bee Science, 2024)
Apivectoring, or bee vectoring, employs managed bees to distribute powders containing disease and pest-fighting biocontrol agents during pollination flights to crops. Our research introduces a novel application of this concept, termed inspensing, which leverages bee vectoring for hive-based benefits. In inspensing, honey bees traverse through a carrier powder combined with products aimed at combating pathogens or pests within the hive. To facilitate this, we developed the ProtectaBEE ® system, an innovative beehive-entrance technology that guides bees through a compartment inoculated with an inspensing powder. This system facilitates the application of beneficial agents into the hive without the need for beekeepers to open the hive, thereby streamlining the treatment process and reducing hive disturbance. To analyze the effectiveness of the system, we employed a fluorescent tracer in a powder formulation to track powder distribution throughout the hive visually. The fluorescent powder was detected in 78.8% of the samples taken for testing and underscores the system's efficacy in delivering material throughout the hive. Complementing this, we inspensed a living dry powderformulated biocontrol agent, Beauveria bassiana, an entomopathogenic fungus known to reduce Varroa mite populations. We used PCR analysis to detect its presence within the hive. B. bassiana was confirmed in up to 86.2% of larvae and 91.7% of mites. Our results affirm the potential for inspensing dry-powder-formulated biocontrol agents to manage Varroa destructor. Inspensing paves new paths for optimizing bee health and pest control strategies, streamlining disease management, simplifying hive maintenance, and minimizing beekeeper intervention, all contributing to sustainable apiculture.